Proteomics approach to identify novel metastatic bone markers from the secretome of PC‐3 prostate cancer cells. Issue 20 (10th July 2017) - Sung, EunJi; Kwon, Oh Kwang; Lee, Jae‐Mok; Lee, Sangkyu
Abstract: Prostate cancer is the leading type of cancer diagnosed, and the most frequent cause of worldwide male cancer‐related deaths annually. The limitations of current prostate cancer screening tests demand the identification of novel biomarkers for the early diagnosis of prostate cancer bone metastasis. In the present study, we performed a proteomic analysis of secreted proteins from the prostate cancer bone metastasis cell line, PC‐3, and the normal prostate cell line, RWPE‐1. We thus quantified 917 proteins, of which 68 were found to be secreted at higher levels by PC‐3 than by RWPE‐1 cells via LC‐MS/MS. To characterize the highly secreted proteins in the PC‐3 cell line and thereby identify biomarker proteins, we divided the quantifiable proteins into four quantitative categories (Q1–Q4). The KEGG lysine degradation and osteoclast differentiation pathways were demonstrated to be enriched in the highly secreted Q4 protein group. Transforming growth factor (TGF) beta family proteins related to osteoclast differentiation were identified as key regulators of PC‐3 cell proliferation. Immunoblotting was used to confirm the observed high level of pentraxin, follistatin, TGF‐beta family members, and serpin B3 secretion by PC‐3 cells. From the collective results of the present study, we suggest that serpin B3 is a promising novel biomarker candidate for the diagnosis of prostate cancer bone metastasis.